Harmonization of Regulation Based on Pancasila Values Through the Constitutional Court of Indonesia - Sudrajat, Tedi (Constitutional Review, 2018)
The legal system which is adopted and applied in Indonesia was based on the formation from the founding fathers which is adjusted to the condition and the spirit of Indonesia as a nation known for its legal system as Pancasila. Ideally, Pancasila serves as the philosophy for the nation of Indonesia, as state's ideology and as the basis of the state. However, in reality, vertical conflicts (government and society) and horizontal conflict (inter-society) have created a variety of concerns, in which the sense of nationalism and diversity has diminished. The trigger is because Pancasila can only be understood as the ideology and the basis of the state, without saturating the meaning contained therein. The paradigm development of Pancasila based on legal state should demand the development of a democratic constitutional state, which juxtaposes the principles of a rule-of-law (nomocracy) with harmonious and complementary principles of the sovereignty of the people (democracy). This role can be solved by the Constitutional Court to harmonize the ideology of Pancasila in the Indonesia legal substance. When the legal development is integrated into meaning, the legal development which characterized by Pancasila can be realized to resolve the variety of community conflicts.